Copper and Bismuth incorporated mixed cation perovskite solar cells by one-step solution process. (April 2021) - Karthick, S.; Hawashin, H.; Parou, N.; Vedraine, S.; Velumani, S.; Bouclé, J.
Highlights: Effect of CuI & BiI 3 partial incorporation into the perovskite solution was studied. Active layer morphological, structural & optoelectronic properties were examined. Reference, CuI & BiI 3 doped PSCs were fabricated, and their performance was analyzed. TPV & preliminary aging tests were carried out to understand the doping mechanisms. Abstract: Last few years, mixed cation/mixed halide FA 0.85 Cs 0.15 Pb ( I 0.85 Br 0.15 ) 3 perovskite planar solar cells have shown remarkable performance with power conversion efficiencies over 21%, making them suitable reference systems among highly efficient and potentially low-cost photovoltaic technologies. Many strategies have been proposed to further improve the electronic quality of the perovskite active layers, such as defect passivation or doping, to demonstrate more robust and stable devices. Doping is indeed a relevant strategy for lead substitution, which is also the main concern towards their commercialization. Here, we systematically investigated the effect of cuprous iodide ( CuI ) and triiodobismuthane ( BiI 3 ) partial incorporation into the reference FA 0.85 Cs 0.15 Pb ( I 0.85 Br 0.15 ) 3 double cation and mixed halide perovskite, from a simple single-step deposition procedure from solution. We especially evaluate the influence of our doping strategy on device performance as a function of the atomic fraction ( x ) of Cu or Bi with regard to Pb, using structural, morphological, and optical characterization techniques. Doped perovskite solar cells, either with Cu or Bi, exhibit reduced performance compared to the undoped reference, which is correlated with the evolution of active layer morphology and structure, along with faster recombination kinetics probed by transient photovoltage measurements. This work further demonstrates to achieve better-performing devices using such doping strategies requires a fine control of the defect states, which are inevitably introduced, and that doping by the trivalent metallic cation ( Bi ) largely perturbs the perovskite structure compared to the substitution of monovalent metal ( Cu ).